Marketing Sales Promotion Girl Perspektif Etika Bisnis Islam - Ridwan, Mohammad; Yolanda, Gita (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2023)
Sales Promotion Girl (SPG) is the spearhead of the company to introduce a product that will be offered to the public. SPG is used as the hand of a company engaged in consumer services. In carrying out promotional activities at the Skechers Grage City Mall Cirebon store, the store requires the right promotional strategy in order to attract the attention of consumers and this strategy is carried out by SPG. This study was conducted to determine the marketing strategy undertaken by sales promotion girl at the store skechers grage City mall Cirebon. This study uses descriptive qualitative methods with data collection using observation, interviews and documentation. The results found in this study are that the marketing sales promotion girl strategy at the Skechers Grage City Mall Cirebon Shoe Store viewed from an Islamic perspective is applied in various ways including advertising promotion mix tools using electronic media such as (Instagram, Facebook and Whatsapp), Personal selling (personal selling) and Sales Promotion. In addition, the promotions carried out are in accordance with Islamic business ethics. Where in applying Islamic values ​​as the implementation of business ethics, there are four things that can be used as guidelines in promotion, namely sincerity, honesty, meaningful, and accountability (responsibility / trustworthiness)